Modeling visuospatial reasoning. Issue 1 (2nd January 2019) - Reed, Stephen K.
ABSTRACT: I apply my proposed modification of Soar/Spatial/Visual System and Kosslyn's (1983) computational operations on images to problems within a 2 × 2 taxonomy that classifies research according to whether the coding involves static or dynamic relations within an object or between objects (Newcombe & Shipley, 2015). I then repeat this analysis for problems that are included in mathematics and science curricula. Because many of these problems involve reasoning from diagrams Hegarty's (2011) framework for reasoning from visual-spatial displays provides additional support for organizing this topic. Two more relevant frameworks specify reasoning at different levels of abstraction (Reed, 2016) and with different combinations of actions and objects (Reed, 2018). The article concludes with suggestions for future directions.